Echolocating Whales and Bats Express the Motor Protein Prestin in the Inner Ear: A Potential Marker for Hearing Loss - Morell, Maria; Vogl, A. Wayne; IJsseldijk, Lonneke L.; Piscitelli-Doshkov, Marina; Tong, Ling; Ostertag, Sonja; Ferreira, Marisa; Fraija-Fernandez, Natalia; Colegrove, Kathleen M.; Puel, Jean-Luc; Raverty, Stephen A.; Shadwick, Robert E. (Frontiers in Veterinary Science, 2020)
Prestin is an integral membrane motor protein located in outer hair cells of the mammalian cochlea. It is responsible for electromotility and required for cochlear amplification. Although prestin works in a cycle-by-cycle mode up to frequencies of at least 79 kHz, it is not known whether or not prestin is required for the extreme high frequencies used by echolocating species. Cetaceans are known to possess a prestin coding gene. However, the expression and distribution pattern of the protein in the cetacean cochlea has not been determined, and the contribution of prestin to echolocation has not yet been resolved. Here we report the expression of the protein prestin in five species of echolocating whales and two species of echolocating bats. Positive labeling in the basolateral membrane of outer hair cells, using three anti-prestin antibodies, was found all along the cochlear spiral in echolocating species. These findings provide morphological evidence that prestin can have a role in cochlear amplification in the basolateral membrane up to 120–180 kHz. In addition, labeling of the cochlea with a combination of anti-prestin, anti-neurofilament, anti-myosin VI and/or phalloidin and DAPI will be useful for detecting potential recent cases of noise-induced hearing loss in stranded cetaceans. This study improves our understanding of the mechanisms involved in sound transduction in echolocating mammals, as well as describing an optimized methodology for detecting cases of hearing loss in stranded marine mammals.